Alternative method for concentration retrieval in differential optical absorption spectroscopy atmospheric gas pollutant measurements - Videla, Fabián Alfredo (2003)
Differential optical absorption spectroscopy is a widely used technique for open-column atmospheric-gas pollution monitoring. The concentration retrieval is based on the fitting of the measured differential absorbance through the Lambert-Beer law. We present an alternative method for calculating the gas concentration on the basis of the proportionality between differential absorbance and differential absorption cross section of the gas under study. The method can be used on its own for single-component analysis or as a complement to the standard technique in multicomponent cases. The performance of the method for the case of cross interference between two gases is analyzed. The procedure can be used with differential absorption cross sections measured in the laboratory or taken from the literature. In addition, the method provides a criterion to discriminate against different species having absorption features in the same wavelength range.